Prevalence of Urinary Tract Infections and Their Antimicrobial Sensitivity Among Diabetic and Non Diabetic Patients in Zakho - Jameel, Ahmed Y.; Artoshi, Diyar M.E. (Science Journal of University of Zakho, 2019)
Urinary tract infection (UTI) is one of the most common bacterial infections in diabetics and non-diabetics. Worldwide about one hundred fifty million people are infected with UTI each year. Indifference in diabetes management has been shown to increase the risk of complications. This may lead to different microbial infections including UTI. UTI is often treated with various broad-spectrum antibiotics due to concerns about infection with resistant organisms. The aim of this study was to determine the prevalence of UTI and antibiotic sensitivity pattern in both diabetic and non-diabetic patients attended the Zakho Emergency Hospital and Chamiskho Health Center at refugee camp in Zakho city. Midstream urine sample was collected from 316 patients attended Zakho Emergency Hospital and Chamiskho Health Center from September 2018 to January 2019 in Zakho city. 316 samples were collected from diabetic and non-diabetics, 195 (61.70%) sample were collected from diabetics and 121 (38.30%) sample were collected from non-diabetic patients. The frequency of male and female was 101 (31.96%) and 215 (68.04%) respectively. The top five dominant bacteria isolated in this study were Escherichia coli (43.20%), Klebsiella pneumoniae (19.90%), Proteus mirabilis (11.65%), Pseudomonas aeruginosa (8.73%) and Staphylococcus aureus (6.31%). The isolated bacteria were highly sensitive to meropenem (100%) followed by imipenem (97% sensitive) and less sensitive to ciprofloxacine, amikacin and nitrofurantoin. While most of the isolates were resistance to tetracycline (21% sensitive), ampicillin (22% sensitive) and piperacillin (28% sensitive). Analysis of the results showed that urinary tract infection is more prevalence in diabetic than non-diabetics and in female than male. Also, the most commonly isolated bacterium was E. coli. Most isolated pathogens show high resistance to tetracycline and ampicillin.